Assessing Environmental Awareness and Attitudes in Higher Education: A Comparison between Environmental and Non-Environmental Discipline - Lidiastuti, Arinda Eka; Purnawati, Wilda (Pedagogi Hayati, 2023)
This article aims to describe environmental awareness and behaviour in biology students and to compare the level of environmental awareness and behaviour among students who take environmental courses to those who do not. The research was on biology college students' environmental awareness and attitude. The sample was 50 using purposive sampling. The research approach was quantitative descriptive. The study was recommended to describe environmental awareness and attitude. The study was also done to determine the level of awareness and environmental behaviour of Biology college students. Researchers employed the Environmental Awareness Test and the Environmental Attitude Scale, created by Dr. Haseen Taj and Dr. K Yeshodara, to gauge participants' levels of environmental awareness. According to the Unpaired T-Test analysis findings, there is a difference in the attitudes and levels of environmental awareness between environmental students and non-environmental students. The p-values for environmental and environmental awareness are 0.049 and 0.024, respectively, less than 0.05. Furthermore, this study paves the way for future research to investigate the underlying factors influencing environmental awareness and attitudes.